Adolescent Social Anxiety as Inner Disharmony: A Platonic Interpretation - Travis Julian; I Ketut Catur Wiguna (Insan Akademika Publications, 2026)
Social anxiety is commonly examined as a psychological condition, but it is less often interpreted as a problem of selfhood and inner order. This article aims to examine how Plato’s ideas can illuminate adolescent social anxiety, especially in relation to low self-esteem, peer pressure, and fear of judgment. The study employs a qualitative conceptual design informed by textual interpretation of Plato’s Republic and a structured integrative review of scholarly literature on social anxiety, self-evaluation, peer relations, and psychological treatment models. The analysis produced four main findings. First, social anxiety can be interpreted as a form of inner disharmony in which external judgment gains disproportionate authority over the self. Second, low self-esteem, peer pressure, and fear of judgment can be read as disruptions in the relation among reason, spirit, and appetite. Third, Plato’s moral psychology helps clarify the ethical and existential dimensions of anxious self-consciousness, especially the tension between appearance and truth. Fourth, Plato’s framework remains interpretively valuable but is insufficient as a complete explanatory or therapeutic model because it does not adequately address developmental, biological, and clinical dimensions of anxiety. The article contributes an interdisciplinary conceptual framework that places Plato in dialogue with contemporary psychology and shows how philosophical reflection may enrich educational and counseling responses without replacing evidence-based treatment